A-2-1 がん治療用イオンによる電離電子密度分布の分析(システムシミュレーション) - 福留, 翔吾; 魚住, 裕介 (バイオメディカル・ファジィ・システム学会大会講演論文集, 2013)
The microscopic information of ion track is essential in the field of the heavy-ion therapy for cancer treatment. The knowledge of effect on human tissue by heavy particle beam is used to develop a reliable medical system of treatment planning. For cancer therapy by radiation, it is important to know the bystander effect. To understand this effect, we have to know the distribution of secondary electron, so we developed a 3D Monte Carlo code. As the demonstration of the developed code for secondary electrons, we calculated the distribution of secondary electrons.